Pharmacokinetics and anti‐nausea effects of intravenous ondansetron in hospitalized dogs exhibiting clinical signs of nausea. Issue 6 (28th July 2022) - Sotelo, Cindy K.; Shropshire, Sarah B.; Quimby, Jessica; Simpson, Sydney; Gustafson, Daniel L.; Zersen, Kristin M.
Abstract: The purpose of this study was to evaluate the pharmacokinetics of intravenous (IV) ondansetron in a population of hospitalized dogs exhibiting clinical signs of nausea. The causes of nausea included pancreatitis, gastroenteritis, endocarditis, chemotherapy‐induced nausea, diabetes mellitus and ketoacidosis, acute kidney injury with aspiration pneumonia, pyometra, uroabdomen, neoplasia, and hepatopathy. Twenty‐four dogs were randomly assigned to one of the following IV ondansetron protocols: 1 mg/kg q12h, 0.5 mg/kg q12h, 1 mg/kg q8h, 0.5 mg/kg q8h. Serum was collected at 0, 0.25, 0.5, 1, 2, 4, 8, 16, and 24 h after the first dose, and nausea scores were recorded at multiple time points. Ondansetron and arginine vasopressin (AVP) concentrations were measured via high‐performance liquid chromatography coupled to tandem mass spectrometry and ELISA, respectively. Noncompartmental pharmacokinetic modeling and dose interval modeling were performed. Ondansetron displayed linear pharmacokinetics. In the 0.5 mg/kg group, mean C max  = 214 ng/ml, AUC0–8h  = 463 ng/ml*h, and calculated half‐life was 1.9 h. In the 1 mg/kg group, mean C max  = 541 ng/ml, AUC0–8h  = 1057 ng/ml*h and calculated half‐life was 1.6 h. Serum ondansetron concentrations were not significantly different between dogs that required rescue anti‐nausea medication (non‐responders) and dogs that did not require rescue therapy (responders). In total, 83.3% of patients in the 0.5 mg/kg q8h, 0.5 mg/kg q12h, and 1 mg/kg q8h groups had improvement in nausea scores. In total, 66.7% of patients in the 1 mg/kg q12h group had improvement in nausea scores. In total, 33% of patients had resolution of nausea in the 0.5 mg/kg q8h, 1 mg/kg q8h, and 1 mg/kg q12h groups, and 16% of patients had resolution of nausea in the 0.5 mg/kg q12h group. AVP concentrations were highly variable and did not correlate with nausea scores. Nausea scores significantly decreased regardless of dosage protocol. AVP was not a reliable biomarker of nausea in this group of dogs.